Tratamento cirúrgico do hiperparatiroidismo primário com pthi intra-operatória - Allen , Miguel (2017)
INTRODUCTION Primary hyperparathyroidism (pHPT) is most frequently caused by a solitary adenoma. Surgical intervention has a high cure rate, particularly when associated with a fast intraoperative intact parathyroid hormone (IOPTH) assay. Aim: to evaluate the performance and accuracy when applying this technique. METHODS we conducted a retrospective study of the last 20 patients with pHPT (mean age 59, range 24-75) that had a surgical intervention in our unit. IOPTH was used in 14 patients, with dosage at 5, 10, 15 and 30 minutes after removal of the adenoma. RESULTS The localization exams had a sensitivity of >75%. The surgical procedure of choice was a unilateral dissection through a 4cm central mini-incision, with all patients experiencing a reduction of >50% of the IOPTH at 10 minutes. There were no surgical complications and the average length of the follow-up period was 11.4 months. The mean calcemia and iPTH dosage progression, from pre-surgery to the last follow-up visit, was respectively of 11 (SD1) to 9.4 (SD0.5) mg/dl and of 233.3 (SD177.5) to 57.1 (SD42) pg/ml. Symptoms improved in all patients.